2000
DOI: 10.1017/s0079497x0000181x
|View full text |Cite
|
Sign up to set email alerts
|

The Lower Palaeolithic Site at Red Barns, Portchester, Hampshire: Bifacial Technology, Raw Material Quality, and the Organisation of Archaic Behaviour

Abstract: The site at Red Barns was excavated in 1975, but the large lithic collection remained unstudied following preliminary examination. This paper reports on further analysis of the lithic material from the site, together with a reappraisal of the faunal remains and original mineralogical analyses, and the results of processing sediment samples from the 1975 excavation. An abundant molluscan assemblage was recovered from the deposits covering the main archaeological horizon, allowing climatic/environmental reconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…So, it was contrary to the raw material hypothesis that pointed handaxes could not be transformed into ovates because of raw material limitations. Additionally, contrary to the reduction model, they showed the existence of refined and symmetrical pointed handaxes, showing intensive reduction (Wenban-Smith et al 2000), obviating the concept of pointed=crude, ovate=refined. The notion of the mental template enables the exploration of cognitive skillswhere such blanks were shaped to produce handaxes with similar morphologies.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…So, it was contrary to the raw material hypothesis that pointed handaxes could not be transformed into ovates because of raw material limitations. Additionally, contrary to the reduction model, they showed the existence of refined and symmetrical pointed handaxes, showing intensive reduction (Wenban-Smith et al 2000), obviating the concept of pointed=crude, ovate=refined. The notion of the mental template enables the exploration of cognitive skillswhere such blanks were shaped to produce handaxes with similar morphologies.…”
Section: Introductionmentioning
confidence: 64%
“…Neither of these models of possible constraints considered some of the arguments related to cultural tradition (Roe 1968;Wenban-Smith et al 2000;Wenban-Smith 2004). The longstanding arguments proposing cultural tradition as the prime influence saw the final morphological characteristics of handaxes reflecting the mental template of the knappers and raw material was selected according to the mental template.…”
Section: Introductionmentioning
confidence: 99%
“…Even allowing for fluvial winnowing (Ashton et al, 2005), one would expect a fluvial deposit such as the Lower Gravel to contain some evidence of handaxe manufacture if any was taking place in the contemporary landscape; 3 investigations at Barnham (Wenban- Smith and Ashton, 1998) have shown that the raw material available to the knappers at the main Barnham Area I Clactonian horizon (the cobble layer) was perfectly suitable for handaxe manufacture. Furthermore, work at Red Barns (Wenban- Smith et al, 2000) has shown that the poor quality frost-fractured raw material at Red Barns was nonetheless used for a handaxedominated industry, even in an area of Chalk bedrock where fresher flint nodules were probably abundant nearby. These observations reduce the impact of raw material availability/ quality as an explanation for why handaxe-manufacturing humans should choose not to do so in certain places.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, material from Hampshire and Dorset has been added from Davis (). Recently‐excavated sites have also been added, including Boxgrove (Roberts and Parfitt, ), High Lodge (Ashton et al ., ), Barnham (Ashton et al ., ), Beeches Pit (Gowlett et al ., ; Preece et al ., , ), Elveden (Ashton et al ., ), the Waechter excavations at Swanscombe (Conway et al ., ), Southfleet Road (Wenban‐Smith, ) and Red Barns (Wenban‐Smith et al ., ). As the TERPS database was originally based on the fluvial record and does not include caves or rockshelters, those of a Lower Palaeolithic or Early Middle Palaeolithic date have been added.…”
Section: Methodsmentioning
confidence: 99%